Atomic Layer Co3O4 Nanosheets: The Key to Knittable Zn–Air Batteries. Issue 43 (1st February 2018) - Chen, Xu; Zhong, Cheng; Liu, Bin; Liu, Zhi; Bi, Xuanxuan; Zhao, Naiqing; Han, Xiaopeng; Deng, Yida; Lu, Jun; Hu, Wenbin
Abstract: Flexible, wearable, and portable energy storage devices with high‐energy density are crucial for next‐generation electronics. However, the current battery technologies such as lithium ion batteries have limited theoretical energy density. Additionally, battery materials with small scale and high flexibility which could endure the large surface stress are highly required. In this study, a yarn‐based 1D Zn–air battery is designed, which employs atomic layer thin Co3 O4 nanosheets as the oxygen reduction reaction/oxygen evolution reaction catalyst. The ultrathin nanosheets are synthesized by a high‐yield and facile chemical method and show a thickness of only 1.6 nm, corresponding to few atomic layers. The 1D Zn–air battery shows high cycling stability and high rate capability. The battery is successfully knitted into clothes and it shows high stability during the large deformation and knotting conditions. Abstract : Atomic layer Co3 O4 nanosheets (1.6 nm thickness) are synthesized by the solvothermal method under the effect of H2 O2 . The atomic layer Co3 O4 nanosheets exhibit high bifunctional activity for the oxygen reduction reaction/oxygen evolution reaction, which is the key to knittable Zn–air batteries. The batteries are successfully knitted into clothes and show high cycling stability and high rate capability.